SEBUAH PENELITIAN MENGENAI KEMAMPUAN SISWA KELAS TIGA DI SMP NEGERI 14 PEKANBARU DALAM MEMAHAMI KEMAMPUAN MEMBACA TEKS NARATIF - Humairoh '; Fadly Azhar; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This is a descriptive research with one try out and real-test design. It aimed to find out the ability of the third year students of SMPN 14 Pekanbaru. The population of this research was all of the third year students at SMPN 14Pekanbaru which consists of 262 students.  Cluster random sampling technique was used to select one class to be the sample. As a result, class IX.1 and IX.2 with 60 students was chosen as the sample. The instrument used was a reading test that consists of 20 questions in the form of multiple choice tests. The results of data showed that mean score in real test was in good level(70.83). Then, according to the results of the data in terms of reading component, the mean score of finding main ideas was 77.92, the mean score of identifying inference was 54.17, the mean score of  finding the meaning of the vocabulary was 91.2, the mean score of finding factual information was 77.8, the mean score of identifying inference was 52.5.